Trips and other stories - Coscolluela, Maria Celeste F. (2008)
Trips and Other Stories is a collection of short fiction. The introduction to the seven pieces is an essay divided into two parts: the first tells the story of the writer's discovery of fiction, while the second takes a look at fiction as an art form and discusses some ideas of technique which influenced the writing of the stories in the collection.